HUBUNGAN PENGETAHUAN PERAWAT TENTANG BASIC LIFE SUPPORT (BLS) DENGAN PERILAKU PERAWAT DALAM PELAKSANAAN PRIMARY SURVEY DI RUANG IGD ROYAL PRIMA HOSPITAL - Karmila Br Kaban (Jurnal Keperawatan Priority, 2018)
Basic Life Support (BLS) is the first-aid action performed to save the life of someone who is experiencing serious conditions, including those who have heart attacks, cardiac arrest and stop breathing. Someone who has stopped breathing or cardiac arrest is not necessarily experiencing death, they can still be helped. By performing first aid measures of Pulmonary Heart Resuscitation (RJP) and primary survey examination. This study was conducted to determine the relationship of nurse knowledge about Basic Life Support (BLS) with the behavior of nurses in the implementation of Primary Survey in Space IGD Royal Prima Hospital Year 2016. This research type is analytic with cross sectional research design, the sample in this study is all nurses in IGD Royal Prima Hospital room is 20 people. Based on the results of chi-square test the relationship between nurse knowledge about Basic Life Support (BLS) with the behavior of nurses in the implementation of Primary Survey in Space IGD Royal Prima Hospital with the degree of significance (α) = 0,05 and df = 1 obtained the calculation result p (0,028) <0,05, hence Ho refused and Ha accepted. In conclusion there is a relationship between nurse knowledge about Basic Life Support (BLS) with the behavior of nurses in the implementation of Primary Survey in Space IGD Royal Prima Hospital Year 2016. In conclusion There is a nurse's knowledge of Basic Life Support (BLS) with Nurse Behavior in Primary Survey at Room of Royal Prima Hospital in Medan IGD 2016. It is expected to Royal Prima Hospital Medan Medan to provide emergency training of PPGD and BTCLS back to nurse for all nurses have a good knowledge of BLS and skilled in the implementation of primary surveys at the IGD.